A set of linear equations to calculate the steady-state operation of an electrical distribution system - Franco, John F. [UNESP]; Rider, Marcos J. [UNESP]; Lavorato, Marina [UNESP]; Romero, Ruben [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2011)
In this paper, the calculation of the steady-state operation of a radial/meshed electrical distribution system (EDS) through solving a system of linear equations (non-iterative load flow) is presented. The constant power type demand of the EDS is modeled through linear approximations in terms of real and imaginary parts of the voltage taking into account the typical operating conditions of the EDS's. To illustrate the use of the proposed set of linear equations, a linear model for the optimal power flow with distributed generator is presented. Results using some test and real systems show the excellent performance of the proposed methodology when is compared with conventional methods. © 2011 IEEE.
Keywords: distributed generation; linear power flow; radial/meshed electrical distribution system; steady-state operation; Constant power; Conventional methods; Distributed generators; Electrical distribution system; Excellent performance; Imaginary parts; Linear approximations; Load flow; Non-iterative; Operating condition; Optimal power flows; Power flows; Real systems; Steady-state operation; System of linear equations; Distributed power generation; Innovation; Smart power grids; Linear equations